2022
DOI: 10.3390/machines10121195
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Reinforcement Learning for Multi-Objective Real-Time Flexible Scheduling in a Smart Shop Floor

Abstract: With the development of intelligent manufacturing, machine tools are considered the “mothership” of the equipment manufacturing industry, and the associated processing workshops are becoming more high-end, flexible, intelligent, and green. As the core of manufacturing management in a smart shop floor, research into the multi-objective dynamic flexible job shop scheduling problem (MODFJSP) focuses on optimizing scheduling decisions in real time according to changes in the production environment. In this paper, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Intelligent manufacturing refers to a new type of manufacturing that can create and deliver products and services through the integrated and intelligent utilization of processes and resources in the information and physical spaces of different system hierarchies [21,22]. With the promotion and application of intelligent manufacturing technology in aerospace and other precision machining fields, intelligent application service demands such as self-awareness, self-decision-making, self-execution, self-learning, and self-optimization have been put made of CNC systems [23].…”
Section: Related Work 21 the Changes Of Cnc Systems In Intelligent Ma...mentioning
confidence: 99%
See 1 more Smart Citation
“…Intelligent manufacturing refers to a new type of manufacturing that can create and deliver products and services through the integrated and intelligent utilization of processes and resources in the information and physical spaces of different system hierarchies [21,22]. With the promotion and application of intelligent manufacturing technology in aerospace and other precision machining fields, intelligent application service demands such as self-awareness, self-decision-making, self-execution, self-learning, and self-optimization have been put made of CNC systems [23].…”
Section: Related Work 21 the Changes Of Cnc Systems In Intelligent Ma...mentioning
confidence: 99%
“…The concatenation result of the concat function is the merging of the calculations from each attention head. The definition of the attention function is given by Equation (22).…”
Section: Encoder and Decodermentioning
confidence: 99%
“…Abebaw et al (2023) [22] considered the JSSP as an iterative decisionmaking problem, and a DDQN is utilized for training the model and learning an optimal policy in which six continuous state features are formulated to record the production environment; an epsilon-greedy strategy is used on the action selection; furthermore, the reward and the penalty of the evaluation metric are designed. Zhang et al (2022) [23] used the PPO algorithm in the DRL framework to tackle the dynamic scheduling problem in a job shop manufacturing system with an unexpected event of the machine failure in which the transport agent is required to dispatch jobs/orders to machines then to sinks from machines after the task of jobs is completed. The proposed framework was validated based on the real-world job shop manufacturing system.…”
Section: Related Workmentioning
confidence: 99%
“…For variant production scenarios, it is indispensable to independently propose the corresponding appropriate multi-objective optimization schemes. In the JSP [4][5][6][7], the product processing of each operation can only be appointed one machine, while the addition of the flexible characteristic in the FJSP [8][9][10][11] can make it more conformed to a real-world production circumstance in which all operations of a product can be processed using more than one available machine. The dynamic JSP or FJSP emphasizes the adaptability of the trained model to handle interruptive incidents and still obtain a complete scheduling solution that is approximately optimal.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation experiments ultimately demonstrated that their proposed framework significantly improves solution quality. Chang et al [45] employed a combination of double-layered Q-learning and deep Q-learning to address multi-objective flexible problems, demonstrating superior solution quality and generalization capability in the obtained results. Lin et al [46] devised two Q-learning-based strategies to enhance the solving capability of local search, substantiating the effectiveness of their approach through a case study.…”
Section: Introductionmentioning
confidence: 99%